1994
DOI: 10.2527/1994.72102709x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of human growth hormone-releasing hormone and photoperiod on hormone release and puberty in dairy heifers1

Abstract: Forty-eight Holstein dairy heifers (98.9 kg BW; 3 mo old) were subjected for 246 d to twice-daily s.c. injections of saline (CTL) or human growth hormone-releasing hormone (GRH; 5 micrograms/kg BW) and to photoperiods of 8 h of light (L): 16 h of dark (D) or 16L:8D according to a 2 x 2 factorial arrangement of treatments. Jugular blood samples were collected from 16 heifers at 3, 4, 8, and 11 mo of age to monitor prolactin, growth hormone, and estradiol-17 beta. Plasma progesterone concentrations were monitore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 41 publications
3
14
0
Order By: Relevance
“…With a lower dose rate of GRF administration of 10, 25, 50 and 100 mg/352 kg body weight a GRF-induced GH peak was registered within 5 -15 min and GH concentrations declined by 20 min after treatment in Holstein steers (Moseley et al 1984), which is similar to the results of the present investigation. Similar peak values of GH were found to occur within 5 -20 min post-injection in dairy calves and heifers (Gluckman et al 1987, Enright et al 1989, 1993, Lapierre et al 1990, Simpson et al 1992, Hongerholt et al 1992, Ringuet et al 1994, Kazmer & Zinn 1998, Kazmer et al 2000, Wiener et al 2000, which further supports the present investigation.…”
Section: Plasma Gh Changes Associated With Grf Administrationsupporting
confidence: 89%
See 4 more Smart Citations
“…With a lower dose rate of GRF administration of 10, 25, 50 and 100 mg/352 kg body weight a GRF-induced GH peak was registered within 5 -15 min and GH concentrations declined by 20 min after treatment in Holstein steers (Moseley et al 1984), which is similar to the results of the present investigation. Similar peak values of GH were found to occur within 5 -20 min post-injection in dairy calves and heifers (Gluckman et al 1987, Enright et al 1989, 1993, Lapierre et al 1990, Simpson et al 1992, Hongerholt et al 1992, Ringuet et al 1994, Kazmer & Zinn 1998, Kazmer et al 2000, Wiener et al 2000, which further supports the present investigation.…”
Section: Plasma Gh Changes Associated With Grf Administrationsupporting
confidence: 89%
“…AUCs for GH response curves increased in GRF-treated bovines (Moseley et al 1984, Petitclerc et al 1987, Enright et al 1989, 1993, Lapierre et al 1990, Simpson et al 1992, Ringuet et al 1994, Kazmer & Zinn 1998, Kazmer et al 2000, Wiener et al 2000, ovines (Hart et al 1985, Della-Fera et al 1986, Kensinger et al 1987, Wheaton et al 1988, Byrem et al 1989, Beermann et al 1990, Godfredson et al 1990, and swine (Takano et al 1985, Dubreuil et al 1990) over placebo. The present study revealed similar observations in GRF-administered growing Murrah buffaloes.…”
Section: Plasma Gh Changes Associated With Grf Administrationmentioning
confidence: 98%
See 3 more Smart Citations